Post harvest quality evaluation of okra (Abelmoschus esculentus (L.) Moench) - Bini N (Department of Processing Technology, College of Agriculture, 2003)
The study on “Post harvest quality evaluation of okra [Abelmoschus esculentus (L.) Moench]” was carried out at the Department of Processing Technology, College of Agriculture, Vellayani, Thiruvananthapuram during 2001-2003. The objective of the study was to evaluate the nutritional quality and shelf life of selected cultivars of okra and thus to identify suitable varieties with better quality and shelf- life. Of the twenty cultivars evaluated Pachalloor Local showed the highest fruit weight. The highest moisture and mucilage content was shown by AE214. Pothencode Local exhibited highest dry matter content. The cultivar selection 13 showed the highest protein and vitamin C content. Fat was highest for AE 275 and calcium for Aruna and the red fruited cultivar. Least crude fibre was shown by Kanjiramkulam Local. All the favourable characters were observed at seven days after flowering. Selection 13 recorded the highest organoleptic quality score. Five cultivars AE 214, AE 219, AE260, selection 13 and Kanjiramkulam Local were selected for shelf- life evaluation based on organoleptic evaluation scores. Changes were observed in all the characters studied under storage for five intervals. Highest fruit weight was shown by AE 214 towards the end of storage. Kanjiramkulam Local exhibited the least crude fibre under storage. Highest mucilage retention was observed in selection 13 and Kanjiramkulam Local. Moisture retention under storage was higher for AE 219. Highest protein, fat and vitamin C retention was observed in selection 13. All the nutrients showed a reducing trend during storage. Towards the end of storage calcium content was highest in AE 260. Highest dry matter content was obtained for AE 214. Highest organoleptic quality scores were recorded for selection 13 towards the end of storage period.